The Application of Jurisprudential Rules to the Fatwas of Islamic Research Academy of Al-azhar in the Outbreak of the New Corona: Towards Building a Scientific Approach Based on Principles, Objectives and Rules of Sharia - Muneer Ali Abdul Rab; Baidar Mohammed Mohammed Hasan; Mahmoud Mohamed Ali Mahmoud Edris; Setiyawan Gunardi; Lutfi Muhammad Zain; Mesbahul Hoque (Usuli Faqih Research Centre PLT, 2024)
Indexed by MyCite